Monkeypox Outbreak - 2022: A Brief Review - Rai, Junu Richhinbung; Rai, Shiba Kumar (Nepal Medical College Journal, 2022)
Monkeypox is a zoonotic viral disease caused by Monkeypox virus belonging to Orthopoxvirus. The virus is present in monkeys and small rodents such as squirrels, ant-eaters and others. First human case was reported from Democratic Republic of the Congo in 1970 and had been reported only from central and western African countries before 2022. This year, the first human case of monkeypox was confirmed on May 7, 2022 in UK who travelled to Nigeria. Thereafter, the disease has caused a multi-country outbreak involving all continents outside Africa. As of August 28, 2022, a total of 47,652 monkeypox cases have been reported from 99 countries that have not historically reported monkeypox and in 7 countries that have historically reported monkeypox. Of the total, 47,209 cases have occurred in countries that have not historically reported monkeypox with a highest numbers of cases (17,431) in USA. Keeping in view of an increasing number of cases “monkeypox emergency” has been declared by US government on August 4, 2022. Second highest numbers of cases have been reported from Spain (6,459), Brazil (3,984), France (3,421), Germany (3,405), Britain (3,207) and following by other countries as of August 28, 2022. No cases has been reported from Nepal as of August 28, 2022.